Abstracts of the 2022 Autumn Meeting of the British Society for Cardiovascular Research - Carolyn Carr (Medical Sciences Forum)
The Autumn Meeting of the British Society for Cardiovascular Research in 2022 was organized by David Grieve, Lauren Kerrigan, Claire Tonry and Chris Watson and held at the Wellcome-Wolfson Institute for Experimental Medicine, Queen’s University Belfast. The theme of the meeting was ‘Cardiac remodeling—basic mechanisms to clinical management’ and included an early career symposium. The Annual Bernard and Joan Marshall Distinguished Investigator Lecture was given by Professor Merry Lindsey on ‘Extracellular matrix remodeling in heart failure’. This paper presents the abstracts selected for oral and poster presentation.